2017
DOI: 10.18632/oncotarget.14540
|View full text |Cite|
|
Sign up to set email alerts
|

Carcinoma-risk variant of EBNA1 deregulates Epstein-Barr Virus episomal latency

Abstract: Epstein-Barr Virus (EBV) latent infection is a causative co-factor for endemic Nasopharyngeal Carcinoma (NPC). NPC-associated variants have been identified in EBV-encoded nuclear antigen EBNA1. Here, we solve the X-ray crystal structure of an NPC-derived EBNA1 DNA binding domain (DBD) and show that variant amino acids are found on the surface away from the DNA binding interface. We show that NPC-derived EBNA1 is compromised for DNA replication and episome maintenance functions. Recombinant virus containing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 54 publications
0
61
0
Order By: Relevance
“…Recently, our laboratory found that an NPC variant of EBNA1 containing 8 amino acid polymorphisms different from the prototypical B95-8 strain, including a T585I substitution, was defective in replication and maintenance of the viral episome (41). The EBNA1 variant was also found to be deficient in suppressing lytic cycle gene transcription and lytic DNA replication (41). We note that the Mutu strain isolated from Burkitt's lymphoma contains both T585P and L582F among 8 additional polymorphisms.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Recently, our laboratory found that an NPC variant of EBNA1 containing 8 amino acid polymorphisms different from the prototypical B95-8 strain, including a T585I substitution, was defective in replication and maintenance of the viral episome (41). The EBNA1 variant was also found to be deficient in suppressing lytic cycle gene transcription and lytic DNA replication (41). We note that the Mutu strain isolated from Burkitt's lymphoma contains both T585P and L582F among 8 additional polymorphisms.…”
Section: Discussionmentioning
confidence: 81%
“…Genetic analyses of various EBV strains indicate that T585 is among the EBNA1 polymorphisms found frequently in both NPC tumors and Burkitt's lymphoma (35)(36)(37)(38)(39)(40)(41). Recently, our laboratory found that an NPC variant of EBNA1 containing 8 amino acid polymorphisms different from the prototypical B95-8 strain, including a T585I substitution, was defective in replication and maintenance of the viral episome (41). The EBNA1 variant was also found to be deficient in suppressing lytic cycle gene transcription and lytic DNA replication (41).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations